STUDI KANDUNGAN LOGAM BERAT (TIMBAL DAN KROMIUM) PADA JENIS KERANG BULU ( ANADARA ANTIQUATA) DI MUARA PANTON, DESA BAGAN ASAHAN, KECAMATAN TANJUNG BALAI, PROVINSI SUMATRA UTARA - Gabryella Damayanty Silaen; Ria Retno; Mardame Pangihutan (Journal of Research and Publication Innovation, 2025)
Muara Panton is an estuary located in Bagan Asahan Village, Tanjung Balai District, Asahan Regency. These waters are known as one of the largest fish producers in North Sumatra Province. Apart from that, it is also used as a ship crossing. The impact of these activities is that heavy metals enter and settle at the bottom of the waters and have a residence time, resulting in contamination by shellfish that will be consumed. This research aims to determine the content of heavy metals lead, copper, chromium and zinc in the feather clam (Anadara atiquanta) in Muara Panton, Bagan Asahan Village, Tanjung Balai District. The implementation is by collecting samples of feather clams (Anadara antiquata) to be tested for heavy metals in the shells to find out the levels of heavy metals found in feather clams in the Panton estuary which will be carried out from July to September 2023. Measurement of the concentration of heavy metals T Lead, Chromium using the Absorption Spectrophotometer (SSA) method. The results of the heavy metal content found in Muara Panton, Tanjung Balai District show that the average heavy metal content of lead is <0.07, chromium with an average of <0.005 mg/kg at all stations with safe limits for consumption of heavy metals lead and chromium in Muara Panton, Bagan Asahan Village, Tanjung Balai subdistrict refers to the PTWI (Provision Tolerable Weekly Intake) value issued by JECFA in FAO/WHO (2004).